Patience, Suffering, and Tolerance: The Experience of Defeat and Exile among the Jesuits of Ethiopia (1632–59) - Cohen, Leonardo (Journal of Jesuit studies, 2022)
This article explores the last letters written by the Catholic patriarch of Ethiopia in exile Afonso Mendes, which illustrate that, in the face of defeat, Mendes has chosen to write the history of martyrdom, the sacrifice, and shedding of blood for the sake of faith. A group requires a sense of connection through a temporary axis. Mendes’s choice in these last years corresponds to the will of generating cohesion in space and continuity in time in a group that has confronted rupture, disillusionment, and deterioration. Mendes might have attempted to establish a framework that would allow him to alleviate the tension caused by the clash between the original aspirations and the flawed fulfillment of the objective. Therefore, the redaction of the processes of martyrdom and the creation of a calendar allows the transition into a place where a harmonious relationship between the past and the present is generated.